Humanized management and social responsibility in credit cooperatives: applications and contributions (Research, Society and Development, 2020)
This study proposes to highlight the different perceptions about the applicability of the assumptions of humanized management, interrelated to the principles of social responsibility, in the daily practices of credit cooperatives, with a view to contributing to the development of cooperativism and territorial development. The methodology used was bibliographic research, documentary research and interviews, based on a case study in an agency of the Sicredi das Culturas RS/MG cooperative, in the northwest of the state of Rio Grande do Sul. The results show that the cooperative strategies and practices applied to stakeholders are interrelated to the concepts of social responsibility and to the assumptions of humanized management, that humanized management strategies and actions are related to the concepts and practices of social responsibility and that this interrelation is established mainly regarding to the systemic vision and dimensions of sustainability. In this way, this research seeks to raise new questions about humanized management and social responsibility and their interrelationship and consequent contribution to the scenario of cooperatives, with a focus on credit cooperatives. It is concluded that humanized management, as a social responsibility strategy, contributes to the optimization of the actions that permeate the cooperative internal and external processes, becoming a valuable and competitive differential for the analyzed agency, for its cooperative and for the Sicredi system , before the market of cooperatives and credit cooperatives, and society.